2019
DOI: 10.1002/jsfa.9660
|View full text |Cite
|
Sign up to set email alerts
|

Application of microwave and ohmic heating for pasteurization of cantaloupe juice: microbial inactivation and chemical properties

Abstract: BACKGROUND: Cantaloupe melon (Cucumis melo L.) is one of the most important dessert fruits and is cultivated in many countries of the world. The effects of microwave (400 and 800 W for 110 s), ohmic (100 and 200 V for 110 s) and conventional heating (27-75 ∘ C for 30 min) treatments on inactivation of Escherichia coli, Salmonella Typhimurium, S. Enteritidis and Staphylococcus aureus pathogens; pH and degradation of vitamin C, -carotene and phenolic compounds of cantaloupe juice were investigated. RESULTS: As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Results showed that the AA content of concentrated samples was lower than the fresh juice (370.9 ± 23.6 mg AA/100 mL). Generally, the heating process reduced the AA content in fruit juice because vitamin C is sensitive to heat and environmental conditions (Hashemi et al ., 2019). AA declines in OHVC treatments were lower than OHAC ( P < 0.05).…”
Section: Results and Decisionmentioning
confidence: 99%
“…Results showed that the AA content of concentrated samples was lower than the fresh juice (370.9 ± 23.6 mg AA/100 mL). Generally, the heating process reduced the AA content in fruit juice because vitamin C is sensitive to heat and environmental conditions (Hashemi et al ., 2019). AA declines in OHVC treatments were lower than OHAC ( P < 0.05).…”
Section: Results and Decisionmentioning
confidence: 99%
“…Several authors have compared the effects of using high and low electric fields on microorganism inactivation. Won et al (2002), Uemura and Isobe (2002), Yildiz and Baysal (2006), Kim, Park, andKang (2018), Hashemi, Gholamhosseinpour, andNiakousari (2019) and found significant reductions in viable cells at higher electric fields; this behaviour was also observed by Shao et al (2019). Moreover, the latter authors showed that the recovery of injured cells is slower at higher voltages.…”
Section: Electric Field Effectsmentioning
confidence: 90%
“…The greater the electric field and shear rate, the lower the inactivation time for a 5-log reduction. Moreover, Hashemi, Gholamhosseinpour, et al (2019) and Hashemi, Mahmoudi, et al (2019) demonstrated that an increase in the electric current had a significant impact on reducing microbial species. This effect was higher for Zygosaccharomyces rouxii than for the bacterial and fungal species analysed, which may suggest that yeasts are more susceptible to electric effects.…”
Section: Electric Field Effectsmentioning
confidence: 99%
“…This may be because β-carotene is prone to degradation and more precisely to isomerization, especially at high temperature, and oxidation, due to the occurrence of oxygen in food (Hashemi et al, 2019;Pénicaud et al, 2011):…”
Section: Total Carotene Contentmentioning
confidence: 99%